Clinical and epidemiological characteristics of monkeypox in a series of cases treated in a health establishment in Peru - Briceño, Monica (2023)
Monkeypox virus infection is a zoonosis caused by a DNA-like virus of the orthopoxvirus. This report describes a series of 12 cases whose mean age was 36 years, with a history of sex among men in 66%; prior to the onset of symptoms, 50% said they had had sex with a stranger. Prodromal symptoms occurred in 90%, between 1 and 4 days characterized by fever, headache, mialgia. The dermal lesions were pustules-vesicles, papules, scabs located mainly on extremities, face-thorax and genitals. All cases had a favorable evolution.